Model of Models Methodology: Reuse Your Architectural Data - Jackson, Aleczander; Palmer, Barrion; Cobb, Daniel (American Journal of Management, 2020)
One of the primary yet underutilized benefits of Model Based Systems Engineering is reuse. Most users of Model Based Systems Engineering lack the understanding of the process involved to develop a project tree that enables use of project data in other projects to facilitate that multi-dimensional reuse. Although the benefits speak for themselves, few practitioners fully grasp the modeling techniques, and rigor, necessary to facilitate a model that is fully traced, modular, and reusable. The Model of Models methodology satisfies these needs, enabling Digital Engineering on the project while realizing significant savings to project time and cost.